Faktor sosial terkait stunting pada anak Suku Lauje usia 24-59 bulan di Kecamatan Palasa, Kabupaten Parigi Moutong - Suwekatama, I Wayan; Kandarina, BJ. Istiti; Purwaningrum, Digna Niken (Jurnal Gizi Klinik Indonesia, 2023)
The social determinants associated with stunting in children from the Lauje tribe (aged 24-59 months) Palasa District, Parigi Moutong RegencyBackground: Stunting is a chronic nutritional problem caused by multiple factors. Stunting is a threat to the achievement of human resource progress. Handling stunting requires an approach according to the characteristics of the region.Objective: This study aims to analyze the social determinants associated with the incidence of stunting in children from the Lauje tribe (aged 24-59 months) Palasa District, Parigi Moutong Regency.Methods: This type of research is observational with a cross-sectional study design and total sample obtained is 130 people. Statistical analysis using Chi-Square test to determine the significance of the relationship between variables.Results: The results of the bivariate analysis showed that the social determinant variables that had a significant relationship with the incidence of stunting were family food security (p=0.0208, OR= 2.56; CI 95%=1.06-6.35), food diversity (p=0.0005, OR=3.61; CI 95%=1.57-8.46), mother’s education (p=0.0002, OR=4.73; CI 95%=1.86-12.68), and family income (p=0.003, OR=2.9; CI 95%=1.33-6.49). While the variables of access to health facilities and access to clean water and sanitation were not related to the incidence of stunting in Lauje children aged 24-59 months.Conclusions: The incidence of stunting in Lauje children was found to be associated with several social determinant variables. So that stunting handling efforts are needed by increasing multi-sectoral collaboration and involving local community leaders.